MODEL PEMBELAJARAN TELAAH YURISPRUDENSI PADA PEMBELAJARAN KETERAMPILAN BERBICARA KRITIS DENGAN MENGGUNAKAN METODE DEBAT KONFRONTATIF - Supratmi, Nunung; Safitri, Heni (Jurnal Pendidikan, 2011)
Creating a societythat has acritical mindmust be taughtto societycontinuallythrough formaland informal education. A school is the formal education is tocreate a generationof intelligentand critical thinkersso they are able to solve their own problems as well as their community problems. To do so, one learning model that can beused isthe learningmodel ofjurisprudence review. This model isverysuitable to useinlearningto speak through the method ofconfrontativedebate. Confrontativedebate on controversialissueswill prompt studentsto criticallyexpress the opinion accompaniedbyargumentsand real evidence.Learningto speakwith the method ofdebateislearningto speak which hasa veryhighdegree of difficulty. Instructionalimpactthat can beachieved throughthis model is thatstudents are ableto think systematicallyaboutthe issue that was developingin the society.